Strategi dalam Meningkatkan Pendidikan Yang Kuat dan Ideal di Sekolah - Hesti Kusumaningrum; Andara Liluyani; Virliana Amanda (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This article was created based on the problems that have occurred in education in Indonesia recently, such as "Is there an event to improve the quality of education in Indonesia?". . The article is obtained from several references such as journals and books that discuss strategies in education. Seeing the problems of education in Indonesia, of course we realize that the role of educators is very important and needed in the learning process. In addition, teachers also need to provide guidance to students who do not understand their learning, or can provide additional classes to students. On the other hand, schools must also have good management and policies for schools, because after all, schools are a place for them to develop, for example, such as providing complete facilities and comfortable classroom conditions when the learning process takes place. The role of parents also needs to be asked in this issue, do these parents care about the importance of education or not? Then parents need to pay attention to the child, whether the child gets a quality education or not.